علاج المخططات - تواتي ابراهيم عيسى (University of Eloued جامعة الوادي, 2024)
ملخص: علاج المخططات (ST) هي مقاربة تكاملية تجمع بين عناصر من العلاج السلوكي المعرفي ، ونظريات التعلق، والعلاجات الجشطالتية والتجريبية. يعتبر هذا النمط من العلاج طريقة فعالة لصياغة وعلاج اضطرابات الشخصية، ويركز على تطور الأعراض المرضية الحالية أكثر من اساليب العلاج المعرفي السلوكي التقليدية، كما تؤكد هذه المقاربة على العلاقة بين المعالج والمريض وقدرتها على التأثير التصحيحي. ويسعى علاج المخططات إلى مساعدة المرضى على فهم احتياجاتهم الانفعالية الأساسية وتعلم طرق تلبية تلك الاحتياجات بشكل تكيفي، وتعمل بشكل مكثف على معالجة ذكريات وتجارب الطفولة المؤذية، والاستناد إلى العديد من التقنيات العلاجية التجريبية لتغيير المشاعر السلبية المتعلقة بهذه الذكريات. ونسعى من خلال هذه المداخلة إلى تسليط الضوء على مسلمات هذه النظرية وأبرز الأساليب العلاجية المستخدمة فيها.Abstract: Schema therapy (ST) is an integrative approach that combines elements from cognitive behavioral therapy, attachment theories, and Gestalt and experiential therapies. This type of therapy is an effective way to formulate and treat personality disorders, and focuses on the development of current pathological symptoms more than traditional CBT methods. This approach also emphasizes the relationship between the therapist and the patient and its ability to corrective effect. Schema therapy seeks to help patients understand their basic emotional needs and learn ways to meet those needs adaptively. It works extensively on the processing of traumatic childhood memories and experiences, and draws on various empirical therapeutic techniques to alter negative feelings related to these memories. We seek, through this intervention, to shed light on the postulates of this theory and the most prominent therapeutic methods adopted by this approach.
الأسس النظرية والفنيات العلاجية
Keywords: علاج المخططات; لعلاج المعرفي السلوكي; اضطرابات الشخصية; Schema therapy; cognitive-behavioral therapy; personality disorders